A new species of Neoscutops Malloch (Diptera: Periscelididae) reared from an ant nest - Carvalho-Filho, Fernando S.; Barbosa, Rodrigo R.; Viana, Talita C. (Zootaxa, 2022)
A new species of Neoscutops Malloch (Diptera: Periscelididae), Neosctups rungae sp. nov., is described from the Brazilian Amazon based on three specimens (2 males and 1 female) reared from carton nests of the ant Azteca aff. chartifex Forel (Formicidae: Dolichoderinae). The new species belongs to the rotundipennis species-group, which is now composed of five valid species. The new species can be readily diagnosed by the following combination of characters: face fully dark brown and surstylus with a basal rounded projection on inner margin.